Gharar dalam Transaksi Ekonomi: Analisis Hukum Islam dan Implikasinya - Atik Devi Kusuma; Lidya Zanti; Wan Elnayla Azzahra; Windi Alya Ramadhani; Wismanto Wismanto (Jurnal Kajian dan Penelitian Umum, 2024)
Gharar, which means uncertainty or speculation in transactions, is a very important concept in Islamic law. In Islam, every transaction is expected to run with transparency and clarity, so that all parties involved can understand their rights and obligations. Transactions containing elements of gharar often harm one party, thus creating injustice. This journal uses a qualitative approach to explore and understand the phenomenon of gharar in the context of Islamic law. This approach will allow for an in-depth view of how gharar is understood, applied, and its implications in business practices. The objectives of this journal are, Analyzing the Concept of Gharar: Identifying and analyzing the definition, characteristics, and categories of gharar in the context of Islamic law according to various sources, including the Quran and Hadith. Recognizing the types of Gharar: Gharar in the object of the transaction, Gharar in price, Gharar in time. And knowing the influence of Gharar in the context of modern economics.